A Digital Home-Based Health Care Center for Remote Monitoring of Side Effects During Breast Cancer Therapy: Prospective, Single-Arm, Monocentric Feasibility Study - Hübner, Hanna; Wurmthaler, Lena; Goossens, Chloe; Ernst, Mathias; Mocker, Alexander; Krückel, Annika; Kallert, Maximilian; Geck, Jürgen; Limpert, Milena; Seitz, Katharina; Rübner, Matthias; Kreis, Philipp; et al. (JMIR Cancer, 2025)
Background: The introduction of oral anticancer therapies has, at least partially, shifted treatment from clinician-supervised hospital care to patient-managed home regimens. However, patients with breast cancer receiving oral cyclin-dependent kinase 4/6 inhibitor therapy still require regular hospital visits to monitor side effects. Telemonitoring has the potential to reduce hospital visits while maintaining quality care. Objective: This study aims to develop a digital home-based health care center (DHHC) for acquiring electrocardiograms (ECGs), white blood cell (WBC) counts, side effect photo documentation, and patient-reported quality of life (QoL) data. Methods: The DHHC was set up using an Apple Watch Series 6 (ECG measurements), a HemoCue WBC DIFF Analyzer (WBC counts), an iPhone SE (QoL assessments and photo documentation), a TP-Link M7350-4G Wi-Fi router, and a Raspberry Pi 4 Model B. A custom-built app stored and synchronized remotely collected data with the clinic. The feasibility and acceptance of the DHHC among patients with breast cancer undergoing cyclin-dependent kinase 4/6 inhibitor therapy were evaluated in a prospective, single-arm, monocentric study. Patients (n=76) monitored side effects—ECGs, WBC counts, photo documentation, and QoL—at 3 predefined time points: study inclusion (on-site), day 14 (remote), and day 28 (remote). After the study completion, patients completed a comprehensive questionnaire on user perception and feasibility. Adherence to scheduled visits, the success rate of the data transfer, user perception and feasibility, and the clinical relevance of remote measurements were evaluated. Results: Mean adherence to the planned remote visits was 63% on day 14 and 37% on day 28. ECG measurements were performed most frequently (day 14: 57/76, 75%; day 28: 31/76, 41%). The primary patient-reported reason for nonadherence was device malfunction. The expected versus the received data transfer per patient was as follows: ECGs: 3 versus 3.04 (SD 1.9); WBC counts: 3 versus 2.14 (SD 1.14); QoL questionnaires: 3 versus 2.5 (SD 1.14); and photo documentation: 6 versus 4.4 (SD 3.36). Among patients, 81% (55/68) found ECG measurements easy, 82% (55/67) found photo documentation easy, and 48% (33/69) found WBC measurements easy. Additionally, 61% (40/66) of patients felt comfortable with self-monitoring and 79% (54/68) were willing to integrate remote monitoring into their future cancer care. Therapy-induced decreased neutrophil count was successfully detected (P<.001; mean baseline: 4.3, SD 2.2, ×109/L; on-treatment: 1.8, SD 0.8, ×109/L). All-grade neutropenia and corrected QT interval prolongations were detected in 80% (55/68) and 2% (1/42) of patients, respectively. Conclusions: Adherence to scheduled remote visits was moderate, with nonadherence primarily attributed to device-related complications, which may have also affected the success rate of data transfer. Overall, patients considered remote monitoring useful and feasible. The prevalence of reported adverse events was comparable to existing literature, suggesting clinical potential. This initial feasibility study highlights the potential of the DHHC.
CRIS-Team Scopus Importer:2025-05-30
Keywords: breast cancer; CDK4/6 inhibitor; cyclin-dependent kinase 4/6 inhibitor; digital medicine; mobile phone; remote monitoring; telehealth

Attrition in the First Three Therapy Lines in Patients with Advanced Breast Cancer in the German Real-World PRAEGNANT Registry - Hartkopf, Andreas D.; Walter, Christina B.; Kolberg, Hans Christian; Hadji, Peyman; Tesch, Hans; Fasching, Peter; Ettl, Johannes; Lüftner, Diana; Wallwiener, Markus; Müller, Volkmar; Beckmann, Matthias; Belleville, Erik; et al. (Geburtshilfe und Frauenheilkunde, 2024)
Background With more effective therapies for patients with advanced breast cancer (aBC), therapy sequences are becoming increasingly important. However, some patients might drop out of the treatment sequence due to deterioration of their life status. Since little is known about attrition in the real-world setting, this study assessed attrition in the first three therapy lines using a real-world registry. Methods Patients with information available on the first three therapy lines were selected from the German PRAEGNANT registry (NCT02338167). Attrition was determined for each therapy line using competing risk analyses, with the start of the next therapy line or death as endpoints. Additionally, a simple attrition rate was calculated based on the proportion of patients who completed therapy but did not start the next therapy line. Results Competitive risk analyses were performed on 3988 1st line, 2651 2nd line and 1866 3rd line patients. The probabilities of not starting the next therapy line within 5 years after initiation of 1st, 2nd and 3rd line therapy were 30%, 24% and 24% respectively. Patients with HER2-positive disease had the highest risk for attrition, while patients with HRpos/HER2neg disease had the lowest risk. Attrition rates remained similar across molecular subgroups in the different therapy lines. Conclusion Attrition affects a large proportion of patients with aBC, which should be considered when planning novel therapy concepts that specifically address the sequencing of therapies. Taking attrition into account could help understand treatment effects resulting from sequential therapies and might help develop treatment strategies that specifically aim at maintaining quality of life.
CRIS-Team Scopus Importer:2024-06-14
Keywords: advanced breast cancer; clinical trials; de novo metastatic breast cancer; recurrent breast cancer metastases

Implementation of CDK4/6 Inhibitors and its Influence on the Treatment Landscape of Advanced Breast Cancer Patients – Data from the Real-World Registry PRAEGNANT - Engler, Tobias; Fasching, Peter; Lueftner, Diana; Hartkopf, Andreas D.; Mueller, Volkmar; Kolberg, Hans-Christian; Hadji, Peyman; Tesch, Hans; Häberle, Lothar; Ettl, Johannes; Wallwiener, Markus; Beckmann, Matthias; et al. (Geburtshilfe und Frauenheilkunde, 2022)
Background Comprehensive data from prospective clinical trials have led to a high level of evidence establishing CDK4/6 inhibitors in combination with endocrine treatment (CDK4/6i + ET) as a standard for the treatment of HER2-negative, hormone receptor-positive (HER2- HR+) breast cancer patients in the first-line advanced therapy setting. Data on patient populations that have been treated in the real-world setting may provide an insight into changes of patient characteristics and prognosis over time. Methods The data were extracted from the prospective real-world registry PRAEGNANT (NCT02338167). Patients had to have HER2- HR+ advanced breast cancer in the first-line metastatic setting. The chosen therapies were described as well as progression-free survival (PFS) and overall survival (OS) in relation to the given therapies and time periods during which they were indicated. Results CDK4/6 inhibitors have been rapidly implemented since their introduction in November 2016. In recent years (2018-2022), about 70-80% of the patient population have been treated with CDK4/6 inhibitors, while endocrine monotherapy was given to about 10% and chemotherapy to about 15% of all patients. The prognosis was worst in patients treated with chemotherapy. Recently, mainly patients with a good prognosis are being treated with endocrine monotherapy, and patients who are treated with chemotherapy have an unfavorable prognosis. The PFS and OS of patients treated with CDK4/6i + ET have remained similar over time despite changes in patient characteristics. Conclusion A treatment with CDK4/6i + ET has rapidly become the therapy standard for patients in the first-line advanced breast cancer setting. After the implementation of CDK4/6i + ET, endocrine monotherapy is only given to patients with a very favorable prognosis, while chemotherapy is provided to patients with a rather unfavorable prognosis. These changes in patient characteristics did not seem to influence the prognosis of patients treated with CDK4/6i + ET.
CRIS-Team Scopus Importer:2022-07-22
Keywords: advanced breast cancer; CDK4/6 inhibitor; chemotherapy; endocrine treatment; real world data

Long-term Follow-up and Safety of Patients after an Upfront Therapy with Letrozole for Early Breast Cancer in Routine Clinical Care – The PreFace Study - Hack, Carolin; Maass, Nicolai; Aktas, Bahriye; Kümmel, Sherko; Thomssen, Christoph; Wolf, Christopher; Kolberg, Hans Christian; Brucker, Cosima; Janni, Wolfgang; Dall, Peter; Schneeweiss, Andreas; Marme, Frederik; et al. (Geburtshilfe und Frauenheilkunde, 2023)
Introduction Adjuvant treatment of patients with early-stage breast cancer (BC) should include an aromatase inhibitor (AI). Especially patients with a high recurrence risk might benefit from an upfront therapy with an AI for a minimum of five years. Nevertheless, not much is known about the patient selection for this population in clinical practice. Therefore, this study analyzed the prognosis and patient characteristics of postmenopausal patients selected for a five-year upfront letrozole therapy. Patients and Methods From 2009 to 2011, 3529 patients were enrolled into the adjuvant phase IV PreFace clinical trial (NCT01908556). Postmenopausal hormone receptor-positive BC patients, for whom an upfront five-year therapy with letrozole (2.5 mg/day) was indicated, were eligible. Disease-free survival (DFS), overall survival (OS) and safety in relation to patient and tumor characteristics were assessed. Results 3297 patients started letrozole therapy. The majority of patients (n = 1639, 57%) completed the five-year treatment. 34.5% of patients continued with endocrine therapy after the mandated five-year endocrine treatment. Five-year DFS rates were 89% (95% CI: 88-90%) and five-year OS rates were 95% (95% CI: 94-96%). In subgroup analyses, DFS rates were 83%, 84% and 78% for patients with node-positive disease, G3 tumor grading, and pT3 tumors respectively. The main adverse events (any grade) were pain and hot flushes (66.8% and 18.3% of patients). Conclusions The risk profile of postmenopausal BC patients selected for a five-year upfront letrozole therapy showed a moderate recurrence and death risk. However, in subgroups with unfavorable risk factors, prognosis warrants an improvement, which might be achieved with novel targeted therapies.
CRIS-Team Scopus Importer:2024-12-16
Keywords: aromatase inhibitors; early breast cancer; hormone therapy; letrozole; prognosis

Mutations in BRCA1/2 and Other Panel Genes in Patients With Metastatic Breast Cancer -Association With Patient and Disease Characteristics and Effect on Prognosis - Fasching, Peter; Yadav, Siddhartha; Hu, Chunling; Wunderle, Marius; Häberle, Lothar; Hart, Steven N.; Rübner, Matthias; Polley, Eric C.; Lee, Kun Y.; Gnanaolivu, Rohan D.; Hadji, Peyman; Hübner, Hanna; et al. (Journal of Clinical Oncology, 2021)
PURPOSE: Among patients with metastatic breast cancer (mBC), the frequency of germline mutations in cancer susceptibility genes and the clinical relevance of these mutations are unclear. In this study, a prospective cohort of patients with mBC was used to determine mutation rates for breast cancer (BC) predisposition genes, to evaluate the clinical characteristics of patients with mutations, and to assess the influence of mutations on patient outcome. PATIENTS AND METHODS: Germline DNA from 2,595 patients with mBC enrolled in the prospective PRAEGNANT registry was evaluated for mutations in cancer predisposition genes. The frequencies of mutations in known BC predisposition genes were compared with results from a prospective registry of patients with nonmetastatic BC sequenced using the same QIAseq method and with public reference controls. Associations between mutation status and tumor characteristics, progression-free survival, and overall survival were assessed. RESULTS: Germline mutations in 12 established BC predisposition genes (including BRCA1 and BRCA2) were detected in 271 (10.4%) patients. A mutation in BRCA1 or BRCA2 was seen in 129 patients (5.0%). BRCA1 mutation carriers had a higher proportion of brain metastasis (27.1%) compared with nonmutation carriers (12.8%). Mutations were significantly enriched in PRAEGNANT patients with mBC compared with patients with nonmetastatic BC (10.4% v 6.6%, P < .01). Mutations did not significantly modify progression-free survival or overall survival for patients with mBC. CONCLUSION: Multigene panel testing may be considered in all patients with mBC because of the high frequency of germline mutations in BRCA1/2 and other BC predisposition genes. Although the prognosis of mutation carriers and nonmutation carriers with mBC was similar, differences observed in tumor characteristics have implications for treatment and for future studies of targeted therapies.
CRIS-Team Scopus Importer:2021-06-04

Occurrence and characteristics of patients with de novo advanced breast cancer according to patient and tumor characteristics – A retrospective analysis of a real world registry - Muller, Volkmar; Hein, Alexander; Hartkopf, Andreas D.; Fasching, Peter; Kolberg, Hans-Christian; Hadji, Peyman; Tesch, Hans; Häberle, Lothar; Ettl, Johannes; Luftner, Diana; Wallwiener, Markus; Beckmann, Matthias; et al. (European Journal of Cancer, 2022)
Background: Patients with de novo metastatic breast cancer (dnMBC) may have different clinical and pathological characteristics. In studies concerned with first-line metastatic patients, the proportion of these patients without secondary resistance mechanisms may have a large influence ont the study results. The aim of this study was to identify patient and tumor characteristics that are associated with dnMBC vs. recurrent MBC (rMBC). Methods: This is a retrospective analysis of data prospectively collected in the PRAEGNANT metastatic breast cancer registry (NCT02338167). Firs line treated patients were eligible. Patient and tumor characteristics were compared with common disease and tumor characteristics relative to de novo metastatic status, as well as early and late recurrences after primary disease without metastases. Results: Among the 947 patients identified, 355 were included with de novo metastatic disease (37.5%). Older age and HER2-positive disease were significantly associated with a higher frequency of dnMBC. Patients younger than 50, 50–69, or 70 years or older had dnMBC frequencies of 22.7%, 44.0%, and 57.6%, respectively. HER2-positive patients had dnMBC at initial presentation in 49.1% of cases, in comparison with 21.9%, 35.5%, and 37.6% in patients with triple-negative, luminal A–like and luminal B–like breast cancer, respectively. Conclusion: Age and breast cancer subtype are associated with the frequency of first-line MBC patients. Inclusion criteria concerning age or breast cancer subtype can influence the frequency of these patients in a selected patient population and can therefore modify the number of patients with secondary resistance to specific therapies in clinical trials.
CRIS-Team Scopus Importer:2022-07-08
Keywords: Advanced breast cancer; Clinical trials; de novo metastatic breast cancer; Recurrent breast cancer metastases

Pembrolizumab in combination with nab-paclitaxel for the treatment of patients with early-stage triple-negative breast cancer – A single-arm phase II trial (NeoImmunoboost, AGO-B-041) - Fasching, Peter; Hein, Alexander; Kolberg, Hans Christian; Häberle, Lothar; Uhrig, Sabrina; Rübner, Matthias; Belleville, Erik; Hack, Carolin; Fehm, Tanja N.; Janni, Wolfang; Hartmann, Arndt; Erber, Ramona; et al. (European Journal of Cancer, 2023)
Background: Pembrolizumab is approved for the neoadjuvant/adjuvant treatment of early triple-negative breast cancer (TNBC) patients in combination with chemotherapy. The Keynote-522 trial used platinum chemotherapy. As neoadjuvant nab-paclitaxel (nP) is also highly effective in triple-negative breast cancer patients, this study investigates the response to nP-containing neoadjuvant chemotherapy in combination with pembrolizumab. Patients and methods: NeoImmunoboost (AGO-B-041/NCT03289819) is a multicenter, prospective single-arm phase II trial. Patients were treated with 12 weekly cycles of nP followed by four three-weekly cycles of epirubicin/cyclophosphamide. Pembrolizumab was given three-weekly in combination with these chemotherapies. The study was planned for 50 patients. After 25 patients, the study was amended to include a pre-chemotherapy single application of pembrolizumab. The primary aim was pathological complete response (pCR), and the secondary aims were safety and quality of life. Results: Of 50 included patients, 33 (66.0%; 95%confidence interval: 51.2%–78.8%) had a (ypT0/is ypN0) pCR. The pCR rate in the per-protocol population (n = 39) was 71.8% (95%confidence interval: 55.1%–85.0%). The most common adverse events of any grade were fatigue (58.5%), peripheral sensory neuropathy (54.7%) and neutropenia (52.8%). The pCR rate in the cohort of 27 patients with a pre-chemotherapy pembrolizumab dose was 59.3%, and 73.9% in the 23 patients without pre-chemotherapy dose. Conclusions: pCR rates after NACT with nP and anthracycline combined with pembrolizumab are encouraging. With acceptable side-effect profiles, this treatment might be a reasonable alternative to platinum-containing chemotherapy in cases of contraindications. However, without data from randomised trials and long-term follow up, platinum/anthracycline/taxane-based chemotherapy remains the standard combination chemotherapy for pembrolizumab.
CRIS-Team Scopus Importer:2023-03-24
Keywords: Neoadjuvant chemotherapy; PD-L1; Pembrolizumab; Triple-negative

Prognosis prediction with the IHC3 score in patients with node-negative, hormone receptor-positive, HER2-negative early breast cancer - Seitz, Katharina; Goossens, Chloe; Hübner, Hannah; Gaß, Paul; Uhrig, Sabrina; Heindl, Felix; Emons, Julius; Rübner, Matthias; Anetsberger, Daniel; Hartmann, Arndt; Beckmann, Matthias; Erber, Ramona; et al. (ESMO Open, 2024)
Background: Prognostication has been used to identify patient populations that could potentially benefit from treatment de-escalation. In patients with hormone receptor-positive (HRpos), human epidermal growth factor receptor 2-negative (HER2neg) early breast cancer (eBC), treatment de-escalation classically involved omitting chemotherapy. With recently developed specialized therapies that require hands-on side-effect management, the therapeutic landscape is changing and therapy decisions are no longer based only on prognosis, but also consider potential side-effects. Therefore, identification of patient groups based on prognostication has gained importance. Materials and methods: In this retrospective analysis, a population of 2359 node-negative HRpos/HER2neg eBC patients was selected from all patients treated at the University Breast Center of Franconia, Germany between 2002 and 2021. The prognostic value of the IHC3 score (incorporating immunohistochemical measurements of the estrogen and progesterone receptor status and Ki-67) with clinical parameters (lymph node status, tumor stage, grading) regarding invasive disease-free survival (iDFS) and overall survival (OS) was assessed. Results: IHC3 positively correlated with Ki-67 expression and inversely correlated with hormone receptor expression. IHC3 categorized into quartiles identified patients with a more unfavorable prognosis: 5-year and 10-year iDFS rates for patients in the highest versus the lowest quartile were 84% versus 95% and 70% versus 88%, respectively. A sensitivity analysis of distant disease-free survival showed similar results to those of iDFS. Five-year and 10-year OS rates for patients in the highest versus the lowest quartile were, respectively, 92% versus 97% and 81% versus 92%. Conclusions: IHC3 is able to define prognostic groups in patients with node-negative, HRpos/HER2neg eBC. Node-negative patients with a high IHC3 score had the worst prognosis, which was comparable to that of node-positive patients described in recent trials. This simple and cost-effective tool could thus potentially aid in identifying patient groups for innovative therapeutic approaches.
CRIS-Team Scopus Importer:2024-11-01
Keywords: early breast cancer; hormone receptor-positive; IHC3; molecular marker; prognosis

Prognostic impact of selection criteria of current adjuvant endocrine therapy trials NATALEE and monarchE in postmenopausal HRpos/HER2neg breast cancer patients treated with upfront letrozole - Fasching, Peter; Hack, Carolin; Nabieva, Naiba; Maass, Nicolai; Aktas, Bahriye; Kümmel, Sherko; Thomssen, Christoph; Wolf, Christopher; Kolberg, Hans Christian; Brucker, Cosima; Janni, Wolfgang; Dall, Peter; et al. (European Journal of Cancer, 2024)
Background: The monarchE and NATALEE trials demonstrated the benefit of CDK4/6 inhibitor (CDK4/6i) therapy in adjuvant breast cancer (BC) treatment. Patient selection, based on clinical characteristics, delineated those at high (monarchE) and high/intermediate recurrence risk (NATALEE). This study employed a historical patient cohort to describe the proportion and prognosis of patients eligible for adjuvant CDK4/6i trials. Methods: Between 2009 and 2011, 3529 patients were enrolled in the adjuvant PreFace clinical trial (NCT01908556). Eligibility criteria included postmenopausal patients with hormone receptor-positive (HRpos) BC for whom a five-year upfront therapy with letrozole was indicated. Patients were categorized into prognostic groups according to monarchE and NATALEE inclusion criteria, and their invasive disease-free survival (iDFS) and overall survival (OS) were assessed. Results: Among 2891 HRpos patients, 384 (13.3 %) met the primary monarchE inclusion criteria. The majority (n = 261) qualified due to having ≥ 4 positive lymph nodes. For NATALEE, 915 out of 2886 patients (31.7 %) met the eligibility criteria, with 126 patients (13.7 %) being node-negative. Patients from monarchE with ≥ 4 positive lymph nodes and NATALEE with stage III BC exhibited the poorest prognosis (3-year iDFS rate 0.87). Patients ineligible for the trials demonstrated prognoses similar to the most favorable patient groups within the eligibility criteria. Conclusion: Patient populations eligible for monarchE and NATALEE trials differed. Nearly a third of the postmenopausal HRpos population, previously under upfront letrozole treatment, met the NATALEE prognostic eligibility criteria. As certain eligible groups had a prognosis similar to non-eligible patients, it might be interesting to explore additional patient groups for CDK4/6i therapy.
CRIS-Team Scopus Importer:2024-08-02
Keywords: Aromatase inhibitors; CDK4/6 inhibitors; Early breast cancer; Hormone therapy; Letrozole; Prognosis

Return of individual genomic research results within the PRAEGNANT multicenter registry study - Hübner, Hanna; Rübner, Matthias; Kurbacher, Christian; Hadji, Peyman; Hartkopf, Andreas D.; Lux, Michael P.; Huober, Jens; Uhrig, Sabrina; Taran, Florin Andrei; Overkamp, Friedrich; Tesch, Hans; Häberle, Lothar; et al. (Breast Cancer Research and Treatment, 2022)
Purpose: The PRAEGNANT study is a registry study for metastatic breast cancer patients, focusing on biomarker detection. Recently, within this study, genetic alterations in 37 breast cancer predisposition genes were analyzed and genetic findings were detected for 396 participants. The aim of this project was to return genetic results to the physicians and to analyze actions taken (e.g., disclosure of results to patients, validation of results, clinical impact, and impact on the patient’s quality of life) using a questionnaire. Methods: 235 questionnaires were sent out to the study centers, with each questionnaire representing one patient with a genetic finding. The questionnaire consisted of twelve questions in the German language, referring to the disclosure of results, validation of test results, and their impact on treatment decisions and on the patient’s quality of life. Results: 135 (57.5%) questionnaires were completed. Of these, 46 (34.1%) stated that results were returned to the patients. In 80.0% (N = 36) of cases where results were returned, the patient had not been aware of the finding previously. For 27 patients (64.3%), genetic findings had not been validated beforehand. All validation procedures (N = 15) were covered by the patients’ health insurance. For 11 (25.0%) patients, physicians reported that the research results influenced current or future decision-making on treatment, and for 37.8% (N = 17) the results influenced whether family members will be genetically tested. Conclusion: This study provides novel insights into the return of research results and into clinical and personal benefits of disclosure of genetic findings within a German registry.
CRIS-Team Scopus Importer:2022-12-02
Keywords: Breast cancer; Genetic testing; Incidental findings; Research results; Return of results

Susceptibility gene mutations in germline and tumors of patients with HER2-negative advanced breast cancer - Fasching, Peter; Hu, Chunling; Hart, Steven N.; Rübner, Matthias; Polley, Eric C.; Gnanaolivu, Rohan D.; Hartkopf, Andreas D.; Hübner, Hanna; Janni, Wolfgang; Hadji, Peyman; Tesch, Hans; Uhrig, Sabrina; et al. (npj Breast Cancer, 2024)
Germline mutations in BRCA1 and BRCA2 (gBRCA1/2) are required for a PARP inhibitor therapy in patients with HER2-negative (HER2−) advanced breast cancer (aBC). However, little is known about the prognostic impact of gBRCA1/2 mutations in aBC patients treated with chemotherapy. This study aimed to investigate the frequencies and prognosis of germline and somatic BRCA1/2 mutations in HER2- aBC patients receiving the first chemotherapy in the advanced setting. Patients receiving their first chemotherapy for HER2- aBC were retrospectively selected from the prospective PRAEGNANT registry (NCT02338167). Genotyping of 26 cancer predisposition genes was performed with germline DNA of 471 patients and somatic tumor DNA of 94 patients. Mutation frequencies, progression-free and overall survival (PFS, OS) according to germline mutation status were assessed. gBRCA1/2 mutations were present in 23 patients (4.9%), and 33 patients (7.0%) had mutations in other cancer risk genes. Patients with a gBRCA1/2 mutation had a better OS compared to non-mutation carriers (HR: 0.38; 95%CI: 0.17–0.86). PFS comparison was not statistically significant. Mutations in other risk genes did not affect prognosis. Two somatic BRCA2 mutations were found in 94 patients without gBRCA1/2 mutations. Most frequently somatic mutated genes were TP53 (44.7%), CDH1 (10.6%) and PTEN (6.4%). In conclusion, aBC patients with gBRCA1/2 mutations had a more favorable prognosis under chemotherapy compared to non-mutation carriers. The mutation frequency of 5% with gBRCA1/2 mutations together with improved outcome indicates that germline genotyping of all metastatic patients for whom a PARP inhibitor therapy is indicated should be considered.
CRIS-Team Scopus Importer:2024-07-19

The impact of physical activity on progression-free and overall survival in metastatic breast cancer based on molecular subtype - Ziegler, Philipp; Hartkopf, Andreas D.; Wallwiener, Markus; Häberle, Lothar; Kolberg, Hans Christian; Hadji, Peyman; Tesch, Hans; Ettl, Johannes; Lüftner, Diana; Müller, Volkmar; Michel, Laura L.; Belleville, Erik; et al. (BMC Cancer, 2024)
Background: Although adequate physical activity has been shown to be beneficial in early breast cancer, evidence in metastatic breast cancer is sparse and contradictory, which could be related to distinct effects of physical activity on the different molecular cancer subtypes. Therefore, we here evaluated the effect of physical activity on progression-free and overall survival (PFS, OS) in metastatic breast cancer, specifically looking at molecular subtypes. Methods: International Physical Activity Questionnaire (IPAQ) questionnaires, filled out by patients enrolled in the prospective PRAEGNANT registry (NCT02338167; n = 1,270) were used to calculate metabolic equivalent task (MET) minutes, which were subsequently categorized into low (n = 138), moderate (n = 995) or high IPAQ categories (n = 137). Cox regression analyses were used to evaluate the impact of IPAQ categories and its interaction with molecular subtypes on PFS and OS. Results: Patient and tumor characteristics were equally distributed across IPAQ categories. HER2pos, HRpos and TNBC were present in 23.1%, 65.7% and 11.2% of patients, respectively. IPAQ scores did not have an impact on PFS and OS in addition to established prognostic factors, either overall or in particular molecular subtypes (PFS: p = 0.33 and OS: p = 0.08, likelihood ratio test). Exploratory analyses showed higher overall survival rates for high IPAQ categories compared to low/moderate IPAQ categories in luminal B-like breast cancer. Conclusions: Self-reported physical activity using the IPAQ questionnaire did not significantly affect PFS or OS in patients suffering from metastatic breast cancer. Nevertheless, some hypothesis-generating differences between molecular subtypes could be observed, which may be interesting to evaluate further.
CRIS-Team Scopus Importer:2024-10-25
Keywords: IPAQ; Metastatic breast cancer; Molecular subtype; Physical activity

Treatment landscape and prognosis after treatment with trastuzumab emtansine - Laakmann, Elena; Emons, Julius; Taran, Florin Andrei; Janni, Wolfgang; Uhrig, Sabrina; Overkamp, Friedrich; Kolberg, Hans Christian; Hadji, Peyman; Tesch, Hans; Häberle, Lothar; Ettl, Johannes; Lüftner, Diana; et al. (Geburtshilfe und Frauenheilkunde, 2020)
Purpose Pertuzumab and T-DM1 are two efficient anti-HER2 treatments for patients with HER2-positive advanced breast cancer. While pertuzumab is usually given in first-line treatment and T-DM1 in second-line treatment, standard therapy options seem to be exhausted up to now after the treatment of patients with these two therapy options. Therefore, it is important to have data that describes the therapy situation and prognosis after T-DM1 treatment. Methods The PRAEGNANT metastatic breast cancer registry (NCT02338167) is a prospective registry for breast cancer patients with a focus on molecular biomarkers. Patients of all therapy lines with any kind of treatment are eligible. Collected data comprises therapies, adverse events, quality of life and other patient reported outcomes. Here we report on the patient characteristics and descriptive prognostic data for HER2-positive patients who have completed a treatment with T-DM1. Therapy patterns after T-DM1 and progression-free survival are reported as well as overall survival. Results A total of 85 patients were identified for the study who were prospectively observed during therapy after the termination of T-DM1. The main reason for T-DM1 termination was progress. Following T-DM1, lapatinib, trastuzumab and chemotherapy were the main therapy choices. Median progression-free survival was 4.8 months (95% CI: 3.2-6.3) and median overall survival was 18.4 months (95% CI: 15.5-21.3). Conclusions Therapy options after T-DM1 in a real-world setting seem to exhibit a relevant clinical efficacy, supporting the concept of continuous anti-HER2 treatments in the advanced therapy setting for breast cancer patients. Novel therapies are needed to improve the rather short median progression-free survival.
CRIS-Team Scopus Importer:2020-11-20
Keywords: advanced breast cancer; antihormone therapy; chemotherapy; HER2 c-erbB2; HER2/neu; lapatinib; metastatic; pertuzumab; T-DM1; trastuzumab